A corrosion failure analysis of copper wires used in outdoor terminal boxes in substation. (April 2019) - Wu, Tangqing; Zhou, Zhaofen; Xu, Song; Xie, Yi; Huang, Lu; Yin, Fucheng
Abstract: Many investigations in the field and laboratory have verified that sulfates and chlorides are the common corrosion products of copper and its alloys in rural and marine atmospheric environments, respectively. However, our field investigation found that a large amount of atacamite appeared in the corrosion products of copper wires in terminal boxes in a rural atmospheric environment. In this paper, SEM, XRD, XPS, electrochemical analysis and ion analysis were collectively used to uncover the essential reasons for this exceptional phenomenon. The experimental results show that the chlorine element in the corrosion product is derived from the Number Tube used to mark the copper wire in terminal boxes. The chloride ion (Cl − ) and relative humidity (RH) are the key factors that affect the corrosion behavior of the copper wire, and the residual stress in the wire is another important factor to accelerate its corrosion. The research results of this paper can enrich the understanding of the corrosion behavior of copper in the atmospheric environment. Highlights: Field investigation found that Cu2 Cl(OH)3 generated in a rural atmosphere. Chlorine element in the corrosion product is derived from number tubes. Chloride ion and RH are the key factors affecting corrosion behavior of copper wire. Residual stress in the wire is another important factor to accelerate its corrosion.